2022
DOI: 10.2147/jaa.s373098
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin 13 rs20541 Gene Polymorphism and Serum Periostin with Asthma and Allergic Conjunctivitis Among Egyptian Patients

Abstract: Background Single nucleotide polymorphisms (SNPs) in the interleukin 13 (IL13) gene are associated with vulnerability to allergic diseases, such as asthma and allergic conjunctivitis (AC). Periostin, as an IL13-induced protein, has emerged as a novel biomarker in several allergic diseases. Data among Egyptian patients are still scarce. Aim To find out the association of IL13 rs20541 gene polymorphism and serum levels of periostin with asthma and AC among Egyptian patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Several studies have evaluated IL-13 gene SNPs in the coding sequence and the promoter region and reported their association with allergic phenotypes; asthma, allergic rhinitis and atopic dermatitis in different ethnic populations [19][20][21][22][23] , however, little data exists concerning their association with INS.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated IL-13 gene SNPs in the coding sequence and the promoter region and reported their association with allergic phenotypes; asthma, allergic rhinitis and atopic dermatitis in different ethnic populations [19][20][21][22][23] , however, little data exists concerning their association with INS.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, allergic reactions are often detected by histamine (HA) and eosinophil cationic protein (ECP) indicators. It has been reported that the degranulation of mast cells promotes a large increases in these two indicators [12]. Eosinophils play a critical role in allergic conjunctivitis and the secretion of the toxic protein, ECP [13].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that various single nucleotide polymorphisms (SNPs) in several interleukin and interleukin receptor genes, including IL-4 and IL-4R [ 25 , 26 , 27 , 28 ], IL-9 [ 29 ], IL-10 [ 30 ], IL-5 and IL5R [ 31 ], IL13 [ 32 ], IL-33 and its receptor IL-1R-like 1 [ 33 , 34 ], IL-18 [ 35 ], IL-13R [ 36 ], and IL-23R [ 37 ], may be linked to an increased risk of developing asthma.…”
Section: Introductionmentioning
confidence: 99%